SYNTHESIS AND CHARACTERIZATION OF GOLD NANOPARTICLES USING TEAK LEAF EXTRACT Tectona grandis - Muhammad Yasser; Setyo Erna Widiyanti; Abdur Rahman Arif (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2017)
Teak leaf extract has been successfully used in the synthesis of gold nanoparticles. It is characterized by a color change of the solution from yellow to red wine after the addition of teak leaf extract to HAuCl4 and the resulting wavelengths in the range of 500-600 nm that indicates that gold nanoparticles have been formed. Growth and stability of the gold nanoparticles produced using UV-Vis Spectroscopy. During observation during 144 hours the stability of gold nanoparticles after 48 hours with a wavelength of about 567.5 -568 nm.